(untitled) (Research, Society and Development, 2022)
Celiac disease (CD) is an autoimmune disease that affects both the epithelium and the lamina propria of the small intestine in individuals who are genetically susceptible and intolerable to gluten. Gluten sensitivity causes villous atrophy, which resolves with a gluten-free diet. When not diagnosed early, CD can have a significant impact on quality of life, mainly related to clinical symptoms such as irritable bowel syndrome and psychiatric disorders. In this sense, this article aims to review the literature on oral and maxillofacial manifestations resulting from Celiac Disease. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The articles were collected from February to July 2022 and covered between the years 2015 to 2022. The main oral manifestations and complications related to celiac disease include enamel hypoplasia, recurrent aphthous ulcerations, dental caries, atrophic glossitis and lichen. plan. The oral manifestations of Celiac Disease can impair the quality of life of patients who complain of discomfort from these lesions. Therefore, it is essential that health professionals are familiar with these disorders, since oral lesions can serve as fundamental indicators in the early diagnosis of the disease.